KORELASI ANTARA RELIGIUSITAS DAN APLIKASI KONSELING DENGAN PERILAKU PENYALAHGUNAAN NARKOBA SISWA SMA NEGERI DI MAKASSAR - Wahyuni Ismail (Faculty of Tarbiyah and Teacher Training Universitas Islam Negeri Alauddin Makassar, 2010)
This research aims at finding out the correlation between religious and counselling application and the trend of the students of SMAN Makassar to use drug. The data are collected by religious scale, counselling application scale, and the scale of drug abuse. The object of the research consists of 956 of XI year class of SMAN Makassar. The data analysis applies Multiple Regression technique. The findings shows that (1) there is a significant corre-lation between religious application and the use of drug of the students of SMAN Makassar, where p = 0,000. (2) The study did not find any significant correlation between counselling application and drug abuse of the students of SMAN Makassar, where p = 0,055.